ETIKA SOSIAL MASYARAKAT TRADISIONAL DALAM EKONOMI DI DESA LAU-LAU KABUPATEN KEPULAUAN ARU DOBO - Sigit Bin Basso (Nusantara Hasana Journal, 2021)
This study aims to find out the social ethics of good behavior in traditional societies in the income economy, 1) how the social ethics of good behavior in traditional societies, 2) how to implement social ethics of good behavior in various aspects of traditional community life, 3) whether social ethics of good behavior are implemented as a whole. in the life of traditional people can get an income economy. This research is descriptive qualitative, while the type of data is qualitative data. This research uses observation, interview and documentation techniques. The results of the study show that the social ethics of good behavior in traditional communities in the economy is carried out by providing in-depth, continuous guidance to the community and the village government.